Maderus: uma metodologia para avaliação do desenvolvimento rural sustentável na agricultura familiar - Hein, André Fernando (2019)
This study aims to develop a methodology for the evaluation of Sustainable Rural Development (DRS) in family farms. Considering that both development and sustainability are multidimensional and must consider at least economic, social and environmental aspects, so we have developed the MADERUS methodology (Sustainable Rural Development Assessment Methodology). This methodology is a type of tool to measure DRS and, from this, promote practical actions to improve sustainability in family farming either by the own farmer or the public policies elaborate for this area. We obtain 33 variables related to sustainability based on a systematic review of national sustainability indicators models, major international models already consolidated, and information collected through interdisciplinary and participatory methodologies realized with doctoral students in DRS. To support the elaboration of the methodology, data were also collected from farmers who socially outstanding and were rewarded and from former family farmers who left their activities and sold their rural property. We sought to analyze these two groups regarding sustainability and unsustainability in family farming. The methodology allows an assessment of the DRS of each rural property by measuring 33 individual indicators, a synthetic index, the IDRS - Sustainable Rural Development Index and ten composite indicators, elaborated from individual indicators thematic groupings. We believe that the differential of the MADERUS methodology in relation to existing ones is that it was conceived in an interdisciplinary way and can be applied to general family farming, regardless of the productive activities explored. This methodology also uses properties satellite images that are compared with the data CAR - Rural Environmental Registry and allows a visual analysis about the environmental adequacy and the soil occupation and conservation. At the validation stage, this methodology was applied to 30 rural properties and compared to the MESMIS methodology, which is internationally consolidated for this purpose. In comparison, MADERUS presented equivalent results to MESMIS, however, in operational and methodological aspects presented advantages, facilitating data collection and tabulation and analysis of results, proving to be adequate for the evaluation of Sustainable Rural Development in family farming.